EXPLORING RURAL INDONESIAN STUDENTS’ AWARENESS AND UNDERSTANDING OF CLIMATE CHANGE THROUGH ENGLISH EDUCATION - Intadani, Masagus Aditya Putra; Inderawati, Rita (English Community Journal, 2026)
This study examines students’ awareness and understanding of climate change through English language learning in a rural senior high school. Using a descriptive quantitative design, 200 students from grades X–XII at SMA Negeri 1 Jejawi completed a 15-item Likert-scale online questionnaire. Data were analyzed using mean scores and standard deviations. Results show that students have a relatively high level of awareness, especially regarding climate change as a global issue, its human causes, and environmental impacts presented in English materials. However, their understanding varies, particularly in higher-order skills such as distinguishing climate from weather, summarizing solution-based texts, and expressing opinions in English. Overall, while English learning supports awareness, greater instructional support is needed to enhance deeper conceptual understanding in rural EFL contexts.